Stem cell genes in atheromatosis: The role of Klotho, HIF1α, OCT4, and BMP4. Issue 10 (17th August 2022) - Mylonas, Konstantinos S.; Karangelis, Dimos; Androutsopoulou, Vasiliki; Chalikias, George; Tziakas, Dimitrios; Mikroulis, Dimitrios; Iliopoulos, Dimitrios C.; Nikiteas, Nikolaos; Schizas, Dimitrios
Abstract: During fetal development, shear stress regulates several aspects of vascular development. Alterations in signaling pathways due to disturbed flow in atheroprone regions closely mirror phenomena seen during embryogenesis. This flow‐dependent dysregulation of developmental genes appears to promote atherogenesis by mediating inflammatory phenomena, cell cycle progression, apoptosis, cell migration, and oxidative stress. Indeed, several stem cell genes have been implicated in vascular health and atheromatosis. Klotho is key in maintaining endothelial integrity, reducing oxidative stress, and sustaining endothelial nitric oxide production. In atherosclerotic lesions, OCT4 mediates the conversion of vascular smooth muscle cells from contractile to a de‐dedifferentiated proliferative phenotype with phagocytic ability. HIF1α drives atherosclerotic plaque progression by promoting intraplaque angiogenesis. BMP4 promotes osteochondrogenic development and arterial calcification. Strategic extracellular matrix changes are also seen during the various phases of atherosclerosis. The aforementioned conceptual framework explains how proatherogenic inflammation develops in response to low shear stress. In the present review, we explored the effect of cardinal atheroprotective ( Klotho, OCT4 ) and proatherogenic ( HIF1α, BMP4 ) genes in mediating proatherogenic inflammation.